2023
DOI: 10.1667/rade-23-00030.1
|View full text |Cite
|
Sign up to set email alerts
|

Noncancer Effects of Ionizing Radiation Exposure on the Eye, the Circulatory System and beyond: Developments made since the 2011 ICRP Statement on Tissue Reactions

Abstract: For radiation protection purposes, noncancer effects with a threshold-type dose-response relationship have been classified as tissue reactions (formerly called nonstochastic or deterministic effects), and equivalent dose limits aim to prevent occurrence of such tissue reactions. Accumulating evidence demonstrates increased risks for several late occurring noncancer effects at doses and dose rates much lower than previously considered. In 2011, the International Commission on Radiological Protection (ICRP) issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 272 publications
0
3
0
Order By: Relevance
“…A growing body of epidemiological evidence has suggested elevated radiation risks of cardiovascular diseases (especially ischemic heart disease and stroke) [ 30 , 31 , 32 , 33 ]; however, the manifestations (in particular at low or moderate doses, and at low dose rates) and mechanistic underpinnings of this remain incompletely understood [ 9 , 34 , 35 ]. Nabialek-Trojanowska et al [ 12 ] carried out speckle-tracking echocardiography in 12 patients at a median of 51 months after radiotherapy for mediastinal lymphoma, concluding that radiation exposure of the heart substructures is correlated with cardiac dysfunction (e.g., left ventricular global or anterior longitudinal strain).…”
Section: Overview Of Published Articlesmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of epidemiological evidence has suggested elevated radiation risks of cardiovascular diseases (especially ischemic heart disease and stroke) [ 30 , 31 , 32 , 33 ]; however, the manifestations (in particular at low or moderate doses, and at low dose rates) and mechanistic underpinnings of this remain incompletely understood [ 9 , 34 , 35 ]. Nabialek-Trojanowska et al [ 12 ] carried out speckle-tracking echocardiography in 12 patients at a median of 51 months after radiotherapy for mediastinal lymphoma, concluding that radiation exposure of the heart substructures is correlated with cardiac dysfunction (e.g., left ventricular global or anterior longitudinal strain).…”
Section: Overview Of Published Articlesmentioning
confidence: 99%
“…Regarding the effects of radiation exposure on the eye, evidence has accumulated for cataracts following moderate or high doses [ 37 , 38 , 39 ] (along with limited evidence at low doses [ 40 , 41 ]) and neovascular glaucoma following high doses [ 9 ]. Azizova et al [ 19 ] reported a significantly increased radiation risk of normal-tension glaucoma (a subtype of primary open-angle glaucoma) in a cohort of Russian Mayak nuclear workers, confirming observations in Japanese atomic bomb survivors [ 42 , 43 , 44 ].…”
Section: Overview Of Published Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Boice et al determined that 109,019 medical professionals linked with radiation procedures between 1965 and 1994 were at an elevated risk for lung cancer [6]. In the healthcare environment, occupational radiation exposure is well-established as a factor that elevates cancer risk and contributes to premature vascular aging and cataract formation [7].…”
Section: Introductionmentioning
confidence: 99%